English Learning in Primary School: A Review of the Literature on Teaching Methods and Strategies - Tiarnita Maria Sarjani Br. Siregar; Nurkholizah; Indah Permata Sari Rambe; Delvita Ayu (International Journal of Education, Vocational and Social Science, 2026)
This study aims to examine and synthesize various methods and strategies of learning English in elementary schools through the Systematic Literature Review (SLR) approach. The data source was obtained from national and international journal articles published in the 2020–2025 period and discussed methods, strategies, and approaches to learning English for young learners. The results of the study show a significant shift from traditional approaches such as the Grammar Translation Method to communicative and student-centered approaches, such as Communicative Language Teaching, Task-Based Learning, Total Physical Response, Direct Method, and storytelling strategies. Communicative and contextual approaches have been shown to be more in line with the characteristics of elementary school students who are active, love concrete activities, and learn through social interaction. In addition, the integration of interactive digital media also increases student motivation and learning participation. However, the implementation of innovative strategies still faces challenges in the form of limited teacher competencies, large class sizes, and uneven infrastructure. Therefore, the use of an integrative approach that combines various methods contextually and adaptively is recommended to optimally improve students' communicative competence.